Employing vanadium dioxide nanoparticles for flexible metasurfaces with switchable absorption properties at near-infrared frequencies. (14th October 2020) - Ko, Byoungsu; Badloe, Trevon; Kim, Soo-Jung; Hong, Sung-Hoon; Rho, Junsuk
Abstract: Using the simple interference interactions in a three-layer thin film structure, absorbers in the near infrared with aesthetically pleasing reflective colouration were designed, fabricated, and characterised. By implementing the phase change material, vanadium dioxide (VO2 ), with its remarkable phase change properties, the absorbers are able to be switched between lower and higher absorption states depending on the external temperature. Conventional fabrication methods involving VO2 require an annealing process after deposition, but here, VO2 nanoparticles dispersed in a polymer mixture were employed to allow the simple and scalable spin coating process to be used, without the need for annealing. This simultaneously opens up the possibility of using flexible substrates for bendable devices. At a temperature of around 68 °C, a change in absorption of around 30% is observed between 800–1600 nm, while the vivid subtractive colours are maintained with almost no observable difference, on both silicon and flexible polymer-based substrates. The fabricated sample is robust to 2500 bending cycles, proving the possibility for scalable VO2 fabrication methods for practical applications.